1988
DOI: 10.1161/01.atv.8.3.288
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E-binding proteins isolated from dog and human liver.

Abstract: Chylomlcron remnant catabollsm appears to be mediated by apolipoprotein (apo) E binding to hepatic llpoprotein receptors. Previously, the apo B.E(LDL) receptor and a unique apo E-blndlng protein (referred to as the apo E receptor) were Isolated from solublllzed canine and human livers. In the present study, the apo E-blndlng fraction was further characterized and found to contain at least three proteins, all of which bind apo E-contalnlng llpoprotelns with high affinity. The 56-kDa band was found to contain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…Martinez et al identified the b chain of ATP synthase, a principal protein complex of the mitochondrial inner membrane, as a high-affinity receptor for HDL that is expressed on the plasma membrane of hepatocytes (69). Interestingly, Beisiegel et al (70) and Mahley et al (71) described almost two decades ago that the b chain of ATP synthase binds apoE-containing lipoproteins with high affinity. It is highly interesting to speculate that in addition to SR-BI, as we demonstrate in this study, the b chain of ATP synthase is the recognition site responsible for displacement of b-VLDL association to hepatocytes by HDL.…”
Section: Discussionmentioning
confidence: 99%
“…Martinez et al identified the b chain of ATP synthase, a principal protein complex of the mitochondrial inner membrane, as a high-affinity receptor for HDL that is expressed on the plasma membrane of hepatocytes (69). Interestingly, Beisiegel et al (70) and Mahley et al (71) described almost two decades ago that the b chain of ATP synthase binds apoE-containing lipoproteins with high affinity. It is highly interesting to speculate that in addition to SR-BI, as we demonstrate in this study, the b chain of ATP synthase is the recognition site responsible for displacement of b-VLDL association to hepatocytes by HDL.…”
Section: Discussionmentioning
confidence: 99%
“…One unit corresponds to 1 ,mol of fatty acid released per min. Protein concentrations were calculated by using the absorbance at 280 nm and the absorption coefficient (A1%) 16.8 cm 1. Human LPL was purified from postheparin plasma by adsorption to heparin/agarose.…”
Section: Methodsmentioning
confidence: 99%
“…Several earlier attempts to characterize the potential apoE receptor protein (15,16) were not successful. Recently, Herz et al (17) described the LDL receptor-related protein (LRP) with the structural potential to be a lipoprotein receptor.…”
mentioning
confidence: 99%
“…It has also been reported that both the ␤-chain and ␣-chain of ATP synthase are receptors for apoE-enriched HDL in the plasma membrane. 23 The possible involvement of the F0/F1-ATPase in the lipid influx/efflux rheostat together with ABCA1 is shown in Figure 1. A fraction of ABCA1 is located in internal endocytic compartments where it may facilitate cholesterol efflux from late endosomes.…”
Section: Abca1-mediated Cholesterol Efflux and Vesicular Traffickingmentioning
confidence: 99%